Passive control of suddenly expanded flow and temperature distribution along the duct at the critical Mach number - Tamboli, Shahid; Sayed, Ahmed Imran Bellary; Abdullah, Roslinda; Monis, Renita Sharon; Khan, Sher Afghan; Jatti, Vijaykumar S.; Kate, Ajit Madhukarrao; Ingole, Yogesh Ramesh; Jilani, Shaikh Sarfaraj (Nature Portfolio (Springer Nature), 2026)
Abrupt relief at the blunt base is common in aerospace because a recirculation zone reduces pressure and increases drag. This study investigates the control of base pressure at Mach 1.0 by using quarter-ribs placed at various points within an axisymmetric duct. CFD simulations with ANSYS Fluent identified the optimal rib size, position, and nozzle pressure ratio (NPR) for either maximizing or minimizing base pressure. Air flows from a converging nozzle into a 16 mm diameter duct, with lengths ranging from L/D = 1 to 6, rib radii from 1 mm to 2.5 mm, and placements from L/D = 0.5 to 2.0. Results demonstrate that ribs significantly impact base pressure by interacting with the shear layer and duct wall. This interaction affects flow reattachment and the pressure differences, which depend on the ribs' size and location. Ribs at 0.5D and 1D slightly increase base pressure, while those at 1.5D and 2D are more effective. Larger rib radii enhance shear layer reattachment, further boosting pressure. Temperature analysis reveals a rise immediately behind the rib, attributed to the increased flow area, followed by a subsequent drop. These findings enable the optimization of passive control strategies in high-speed aerodynamics, thereby improving system reliability, reducing costs, increasing fuel efficiency, and supporting environmental goals.